Factor Affecting User Satisfaction of Property Management Helpdesk Mobile Application Using End User Computing Satisfaction (EUCS) Modification Model - Rahmat Maulana, Ihsan; Nilo Legowo (International Journal of Advances in Data and Information Systems, 2025)
The property industry has benefited from ongoing technological advancements in apartment management. In Indonesia, apartments are among the fastest-growing real estate types. Consequently, tenants face greater competition for quality services, especially in helpdesk support. The property management helpdesk application is a modern solution developed by the property business to improve service delivery. Tenants can submit requests and complaints directly through mobile apps. This study employs a modified End User Computing Satisfaction (EUCS) model to evaluate user satisfaction with the helpdesk application. Additional variables include system quality, perceived usefulness, and attitude toward use. A simple random sampling strategy and quantitative methodology were applied. Primary data were collected through questionnaires from 336 users of the property management helpdesk application. Findings indicate that system quality, content, accuracy, format, ease of use, and timeliness positively affect users’ attitudes toward the application. The results also show that both system quality and attitude toward use have a significant positive impact on user satisfaction. These data provide valuable insights for improving the application functionalities and user experience. The findings assist property management in improving service quality via enhanced application performance, elevating user happiness and renter retention in a competitive property landscape.